Social and psychological impact of musical collective creative processes in virtual environments; The Avatar Orchestra Metaverse in Second Life - Martín, Gema F.B. (Musica/Tecnologia, 2018)
Social networks, date webs, multi-player online games and other technological resources enabling remote personal interactions have a rising social impact that is changing some paradigms of the human relationships. The rise of such impact is determining that governs are adapting their legal system to affront new challenges arising from those new technologies. In this paper, it has been assessed whether personal interaction trough immersive virtual environments allow, or even enhances, collective creativity thanks to technological features as described below. First, the possibility to overcome technological barriers found in the physical world. Second, a different symbolic connection emerges from the lack of face-to-face contact. Third, individuals should focus their attention on the environment, in this case, Second Life (SL), during the rehearsal. Fourth, the wide diversity of age, ethnic and geographical features of the participants. To assess these insights, a case-study, focused on the Avatar Orchestra Metaverse (AOM), an orchestra based on SL, has been performed based on a participative observation, where valuable parameters have been identified during an immersive experience of the researcher. After then, participants of the case-study orchestra were subjected to specific test describing their experience and impressions at the social and creative levels in Second Life. Thus, it has been found that, in the AOM, the virtual environment could have created an appropriate space promoting the collective creativity.